Catalytic and Noncatalytic Conversion of Methane to Olefins and Synthesis Gas in an AC Parallel Plate Discharge Reactor - Mohammad Ali Khodagholi; Mohammad Irani (Journal of Chemistry)
Direct conversion of methane to ethylene, acetylene, and synthesis gas at ambient pressure and temperature in a parallel plate discharge reactor was investigated. The experiments were carried out using a quartz reactor of outer diameter of 9 millimeter and a driving force of ac current of 50 Hz. The input power to the reactor to establish a stable gas discharge varied from 9.6 to maximum 15.3 watts (w). The effects of ZSM5, Fe–ZSM5, and Ni–ZSM5 catalysts combined with corona discharge for conversion of methane to more valued products have been addressed. It was found that in presence or absence of a catalyst in gas discharge reactor, the rate of methane and oxygen conversion increased upon higher input power supplied to the reactor. The effect of Fe–ZSM5 catalyst combined with gas discharge plasma yields C2 hydrocarbons up to 21.9%, which is the highest productions of C2 hydrocarbons in this work. The effect of combined Ni–ZSM5 and gas discharge plasma was mainly production of synthesis gas. The advantage of introducing ZSM5 to the plasma zone was increase in synthesis gas and acetylene production. The highest energy efficiency was 0.22 mmol/kJ, which belongs to lower rate of energy injection to the reactor.